Metabolite profiles and DNA methylation in metabolic syndrome: a two-sample, bidirectional Mendelian randomization - Jones, Alana C.; Ament, Zsuzsanna; Patki, Amit; Chaudhary, Ninad S.; Srinivasasainagendra, Vinodh; Kijpaisalratana, Naruchorn; Absher, Devin M.; Tiwari, Hemant K.; Arnett, Donna K.; Kimberly, W. Taylor; Irvin, Marguerite R. (Frontiers in Genetics, 2023)
Introduction: Metabolic syndrome (MetS) increases the risk of cardiovascular disease and death. Previous ‘-omics’ studies have identified dysregulated serum metabolites and aberrant DNA methylation in the setting of MetS. However, the relationship between the metabolome and epigenome have not been elucidated. In this study, we identified serum metabolites associated with MetS and DNA methylation, and we conducted bidirectional Mendelian randomization (MR) to assess causal relationships between metabolites and methylation. Methods: We leveraged metabolomic and genomic data from a national United States cohort of older adults (REGARDS), as well as metabolomic, epigenomic, and genomic data from a family-based study of hypertension (HyperGEN). We conducted metabolite profiling for MetS in REGARDS using weighted logistic regression models and validated them in HyperGEN. Validated metabolites were selected for methylation studies which fit linear mixed models between metabolites and six CpG sites previously linked to MetS. Statistically significant metabolite-CpG pairs were selected for two-sample, bidirectional MR. Results: Forward MR indicated that glucose and serine metabolites were causal on CpG methylation near CPT1A [B(SE): −0.003 (0.002), p = 0.028 and B(SE): 0.029 (0.011), p = 0.030, respectively] and that serine metabolites were causal on ABCG1 [B(SE): −0.008(0.003), p = 0.006] and SREBF1 [B(SE): −0.009(0.004), p = 0.018] methylation, which suggested a protective effect of serine. Reverse MR showed a bidirectional relationship between cg06500161 (ABCG1) and serine [B(SE): −1.534 (0.668), p = 0.023]. Discussion: The metabolome may contribute to the relationship between MetS and epigenetic modifications.